CONCERNING LATEST TECHNOLOGIES APPLICATION IN FORENSIC PRACTICE UNDER CONDITIONS OF DIGITALIZATION - Grekova, Liliia; Myronets, Oksana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Scientific-technological progress affects all spheres of human life. Forensic practice is not an exception. Purpose of the study is to analyze the application of new technologies in forensic practice in the context of digitalization. Achieving this goal is ensured through the search for scientific-theoretical constructions and analysis of some innovative technologies of today. Research methods of the work are a comprehensive approach to the analysis of the application of new technologies in the context of digitalization. It is based on the dialectical method of research, analytical, formal-logical and comparison. Results are the conclusion that in Ukraine there is a problem of legislative and financial support for the use of new technological tools in forensic practice. Equally important issues in this area that need attention from scientists and legislators with relevant proposals at the regulatory level are: a legal status of unmanned aerial vehicles, ensuring of person’s confidentiality, data protection and privacy, the use of artificial intelligence in preventive police work, as well as scientific understanding of the Internet of Things and a legal status of persons with integrated implants. Discussion of the obtained results is that the paper attempts to show and analyze the problem of using the latest technologies in forensic practice. The general theoretical understanding of innovations for their application in forensic practice in modern conditions is clarified, some types of new technologies that have their application in the practical forensic activity in the digital times are investigated, some prospects of solving problems of new technologies application in forensic practice in digitalization era are outlined.